Comparative Analysis of Armed Resistance for Independence in the Baltic Countries and Ukraine - Anušauskas, Arvydas (Genocidas ir rezistencija, 1997)
The movements for national independence in the western part of the former Soviet Union, or the Molotov–Ribbentrop Pact zone, organised an armed struggle against the Soviet occupiers in 1944–1953. In western Ukraine, the struggle for the creation of a nation–state has been waged since 1918 against all the states that have alternately ruled its territory – Poland, the Soviet Union, and Germany. The armed struggle for independence by the national movements of the Baltic states and western Ukraine between 1945 and 1953 became a decisive factor. The aim of this article is to reveal the characteristics of these movements based on statistical documents from the Soviet military suppression structures. The main force of military suppression was the Soviet Union’s internal army.